Role of self-help groups in promoting micro enterprises through micro credit: an empirical study - Kumaran, K.P. (2002)
In recent years, the individual approach to poverty allevication programmes has been increasingly replaced by group mode. This is particularly experienced in delivering micro finance to the poor. Studies have shown that the delivery of micro finance to the poor is smooth, effective and less costly if they are organised into Self Help Groups (SHG). The present study is primarily intended to document the experiences in SHGs in promoting micro enterprises through micro credit intervention. The study was conducted in the Pune district of Maharashtra State. For the purpose of the study 15 sample cases of SHGs were selected on a random basis. among them 10 groups were promoted jointly by NGO and Bank. While the remaining five of them were formed by District Rural Development Agency. From the selected SHGs 90, members were interviewed to study the structure and operation of SHG. Further, 29 entrepreneurs selected from the group were interviewed to study in detail the promotion, functioning and sustainability of micro enterprises. - Reproduced.
Keywords: Credit; Financial institutions; Poverty; Self help; Small scale industry